Conformational Dependence of Triplet Energies in Rotationally Hindered N‐ and S‐Heterocyclic Dimers: New Design and Measurement Rules for High Triplet Energy OLED Host Materials. Issue 21 (10th March 2021) - Wright, Iain A.; Danos, Andrew; Montanaro, Stephanie; Batsanov, Andrei S.; Monkman, Andrew P.; Bryce, Martin R.
Abstract: A series of four heterocyclic dimers has been synthesized, with twisted geometries imposed across the central linking bond by ortho ‐alkoxy chains. These include two isomeric bicarbazoles, a bis(dibenzothiophene‐ S, S ‐dioxide) and a bis(thioxanthene‐ S, S ‐dioxide). Spectroscopic and electrochemical methods, supported by density functional theory, have given detailed insights into how para ‐ vs. meta ‐ vs. broken conjugation, and electron‐rich vs. electron‐poor heterocycles impact the HOMO–LUMO gap and singlet and triplet energies. Crucially for applications as OLED hosts, the triplet energy ( E T ) of these molecules was found to vary significantly between dilute polymer films and neat films, related to conformational demands of the molecules in the solid state. One of the bicarbazole species shows a variation in E T of 0.24 eV in the different media—sufficiently large to "make‐or‐break" an OLED device—with similar discrepancies found between neat films and frozen solution measurements of other previously reported OLED hosts. From consolidated optical and optoelectronic investigations of different host/dopant combinations, we identify that only the lower E T values measured in neat films give a reliable indicator of host/guest compatibility. This work also provides new molecular design rules for obtaining very high E T materials and controlling their HOMO and LUMO energies. Abstract : A new series of high E T heterocyclic dimers has been synthesized with large dihedral angles enforced by steric hindrance. A meta ‐conjugated carbazole dimer displays the highest E T of 3.07 eV in dilute polymer film, however in a neat film this falls to 2.83 eV. Similar variation is observed across the series. This work highlights that to reliably estimate host/guest compatibility, E T determined from phosphorescence of neat films must be reported for new host materials. The currently accepted practice of reporting values from frozen solution or polymer films is no substitute.